PENGARUH ADOPSI IFRS, POLITICAL COST, DAN LITIGATION RISK TERHADAP KONSERVATISME AKUNTANSI (Studi Empiris Terhadap Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2016-2018) - Novitasari Novitasari; Moh. Amin; Hariri Hariri (Universitas Islam Malang, 2020)
The purpose of this study was to determine the effect of Adoption of International Financial Reporting Standards (IFRS), Political Cost, and Litigation Risk Against Accounting Conservatism. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange in 2016 - 2018. Samples selected by use purposive sampling and get 63 companies based on criteria. This research uses multiple linear regression model. The results of this study indicate that the adoption of International Financial Reporting Standards (IFRS), Political Cost, and Litigation Risk influences Accounting Conservatism. The adoption of the International Financial Reporting Standards (IFRS) has a negative effect on Accounting Conservatism. Political Cost has a positive effect on Accounting conservatism. Political Cost has a positive effect on Accounting Conservatism.Keywords: IFRS, Political Costs, Litigation Risk, Accounting Conservatism.